2016
DOI: 10.1038/srep26838
|View full text |Cite
|
Sign up to set email alerts
|

Open and closed evolutionary paths for drastic morphological changes, involving serial gene duplication, sub-functionalization and selection

Abstract: Twin-tail goldfish strains are examples of drastic morphological alterations that emerged through domestication. Although this mutation is known to be caused by deficiency of one of two duplicated chordin genes, it is unknown why equivalent mutations have not been observed in other domesticated fish species. Here, we compared the chordin gene morphant phenotypes of single-tail goldfish and common carp (close relatives, both of which underwent chordin gene duplication and domestication). Morpholino-induced knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…). Taking previous reports into consideration (Watase, ; Koh, , ; Asano and Kubo, ; Smartt, ; Abe et al, , ), we will further discuss how selective pressure, polymorphisms, and molecular mechanisms are related with our observations of developmental variations in the context of evolutionary developmental biology.…”
Section: Discussionmentioning
confidence: 91%
“…). Taking previous reports into consideration (Watase, ; Koh, , ; Asano and Kubo, ; Smartt, ; Abe et al, , ), we will further discuss how selective pressure, polymorphisms, and molecular mechanisms are related with our observations of developmental variations in the context of evolutionary developmental biology.…”
Section: Discussionmentioning
confidence: 91%
“…In fact, the injection of MOs that target either of the szl paralogues in single‐tail common‐goldfish embryos was sufficient to reproduce the bifurcated caudal fin and its primodia (Figures and e,f; Supporting Information Figure S1). Therefore, the szl paralogues are not functionally redundant and cannot rescue each other, unlike other paralogous gene sets that exhibit partial redundancy, incomplete non‐functionalization, or neo‐functionalization (Figure ; Abe et al., ; Force et al., ; Innan & Kondrashov, ; Rastogi & Liberles, ; Sémon & Wolfe, ). Our results suggest that the absence of szl ‐type twin‐tail goldfish in domesticated populations is not due to buffering mechanisms between szl paralogues.…”
Section: Discussionmentioning
confidence: 99%
“…In the common carp, it was reported that the chd gene paralogues are expressed at early embryonic stages in a completely overlapping manner. Thus, the depletion of a single chd gene paralogue did not produce any notable phenotypes at late larval stages (Abe et al., ; Sémon & Wolfe, ). In this report, we examine the presence/absence of szl gene paralogues and whether the depletion of the szl gene can cause the twin‐tail morphology in goldfish.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, our previous study reported a conservative evolutionary process for the chdA and chdB genes in common carp, based on their gene expression patterns. Moreover, an equivalent stop codon allele for chdA has not been found in our previous studies or publicly available genomic data for the common carp (Abe et al, , ; Xu et al, ). These major differences lead us to ask the question of why the chdA and chdB paralogues have evolved in such a different manner in the two closely related lineages of goldfish and common carp, which shared a genome duplication and were both domesticated.…”
Section: Discussionmentioning
confidence: 60%
“…These major differences lead us to ask the question of why the chdA and chdB paralogues have evolved in such a different manner in the two closely related lineages of goldfish and common carp, which shared a genome duplication and were both domesticated. Furthermore, our analyses could not sufficiently explain why the branch length of the goldfish chdB gene is longer in comparison with some other chordin genes in the phylogenetic tree (Abe et al, , ; Figure B). More specifically, our molecular developmental genetics led us to conclude that while the chdA gene highly contributed to morphological evolution, the nucleotide sequence of chdB evolved faster than that of chdA , suggesting the conservative nature of chdA gene sequence.…”
Section: Discussionmentioning
confidence: 66%